2012
DOI: 10.1097/yco.0b013e3283503669
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and mental health

Abstract: Despite some yet to be resolved challenges, the concept of emotion regulation has a broad and significant heuristic value for research in mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
210
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 646 publications
(234 citation statements)
references
References 81 publications
15
210
0
9
Order By: Relevance
“…Berking & Wupperman, 2012;Gross & John, 2003;Gross & Muñoz, 1995). A recent meta-analysis suggested that rumination may have the strongest associations with psychopathology compared to other ER strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Berking & Wupperman, 2012;Gross & John, 2003;Gross & Muñoz, 1995). A recent meta-analysis suggested that rumination may have the strongest associations with psychopathology compared to other ER strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At work, people often must cope with difficult situations and solve problems while also addressing the challenging emotions that arise in those situations. Because deficits in the ability to adaptively cope with difficult emotions are related to various mental health problems (64), the use of effective emotion-regulation techniques (65) in low-threshold internet-based stressmanagement training appears promising (66,67).…”
Section: Study Limitationsmentioning
confidence: 99%
“…More precisely, emotional reactivity and the ability to down-regulate negative emotions are needed to show empathy, a key ingredient for therapy success (Elliott et al, 2011;Markowitz & Milrod, 2011;Rogers, 1957). Besides facilitating empathy, effective emotion regulation helps psychotherapists to model effective emotion regulation to patients (Paivio, 2013) and to safeguard their own well-being and mental health (Berking & Wupperman, 2012), which are prerequisites for effective functioning at work (Wright & Cropanzano, 2000). The latter aspect is critical, as PSYCHOTHERAPISTS AND NEGATIVE EMOTIONS 11 psychotherapists are at risk of mental health problems and vicarious traumatization (Pearlman & Mac Ian, 1995), which, if not avoided, might interfere with their therapeutic effectiveness (Sherman, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Besides facilitating empathy, effective emotion regulation has additional benefits for psychotherapists. Given that dysfunctional emotion regulation is thought to underlie the etiology of many mental health problems (Berking & Wupperman, 2012), a psychotherapist's role often involves modeling more effective emotion regulation for their patients (Paivio, 2013). Furthermore, ineffective emotion regulation makes the psychotherapist vulnerable to vicarious traumatization, which can result from repeated exposure to narratives about negative life events, such as abuse and victimization (Pearlman & Mac Ian, 1995).…”
mentioning
confidence: 99%